The electivity of public authorities in the Russian Federation and the Russian pre-revolutionary electoral qualification system - A. Kostyukov (Pravoprimenenie, 2018)
The subject. The article explores the principle of electivity as the principle of organization the public power in the Russian Empire, Soviet Russia and in the modern Russian Federa-tion.The purpose of this paper is to show how the principle of electivity developed in the Russian Empire, Soviet Russia and in the modern Russian Federation and to demonstrate Russian qualification electoral system.The methodology. The author uses a dialectical method, a method of analysis and synthesis, a formal legal method, a comparative legal method.Results, scope of application. Qualification principle in electoral system has undergone var-ious changes in various periods of Russian history. The Zemsky reform of 1864 and the Ur-ban reform of 1870 are analyzed in context how they significantly expanded the electoral rights of citizens. The positive results of the reforms were minimized by the Urban and Zem-sky counter-reforms of Emperor Alexander III. The author shows the negative consequences of the counter-reforms of Alexander III on the example of the second capital of the Russian Empire – Moscow.After the October Revolution, the electoral legislation included new elements of the censor-ship system that extended to the class enemies of the Soviet government. In general, during the Soviet period, general, equal, direct elections were declared in the Constitution. Sepa-rately post-Soviet electoral system in Moscow as the city of federal significance is examined.In the 1990s and 2000s the revival of the Russian electoral system was taking place. In ad-dition, there is a transformation of the principle of election of bodies and officials of local self-government.The author comes to the conclusion that some elements of the census system in the mod-ern interpretation remain in the current legislation. In fact, direct elections at different lev-els of government are replaced by indirect elections or the appointment of elected bodies and officials using a modern system of electoral qualifications, that directly contradict the Art. 3 of the Constitution of the Russian Federation.